Pengaruh Harga Kompetitif, Kualitas Produk dan Lokasi Terhadap Keputusan Pembelian Pada PT Esa Solusi Mandiri - Oktavio Mi’roj Rofik; Sri Lestari (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine the influence of competitive prices, product quality and strategic location on buying decisions at PT. Esa Solusi Mandiri in Surabaya. Competitive prices certainly have a significant impact on buying decisions. PT. Esa Solusi Mandiri in the 2021-2023 period experienced an increase in sales. It cannot be denied that price, product quality and location are strongly supports in influencing buyer decision at PT. Esa Solusi Mandiri.